Baseline Features, Treatment Choice and Early Frontline TKI Permanent Discontinuation in Younger Patients with Chronic Myeloid Leukemia: A “Campus CML” Study - Cavazzini, Francesco; Capodanno, Isabella; Miggiano, Maria Cristina; Bucelli, Cristina; Leonetti Crescenzi, Sabrina; Russo, Sabina; Carmosino, Ida; Romano, Atelda; Sorà, Federica; Bonifacio, Massimiliano; Luciano, Luigiana; Caocci, Giovanni; et al. (Blood, 2023)
Introduction Median age at diagnosis in patients with Chronic Myeloid Leukemia (CML) is about 60 years: only few data are available in younger subjects at present. Aim To analyze initial features, choice of frontline Tyrosine-Kinase Inhibitor (TKI) and early adverse events leading to permanent TKI discontinuation in the first 12 months from TKI start in newly diagnosed subjects aged ≤ 40 years in a large and unselected real-life cohort of CML patients. Methods We retrospectively evaluated 1963 patients newly diagnosed from 1/2012 to 12/2019 at 38 Hematology Centers in Italy participating at the “Campus CML” project: according to age at diagnosis, 302 were ≤ 40 years [Younger Patients (YP)], 900 were > 45 < 65 years [Intermediate Aged Patients (IAP)] and 761 were ≥ 65 years [Elderly Patients (EP)]. Results Clinical features, frontline TKI and causes of early TKI discontinuation according to age at diagnosis are reported in the Table 1. As to baseline clinical features, YP had significantly higher WBC count, lower Hb levels and higher rate of spleen enlargement: moreover, as expected, low-risk Sokal score was more common and rate of concomitant diseases/number of concomitant drugs lower in YP. As to frontline TKI, 96 YP (31.1%) received imatinib (IM) and 206 (68.9%) a 2G-TKI [dasatinib (DAS) n=60, 19.9%; nilotinib (NIL) n=144, 47.6%]: choice of 2G-TKI as frontline treatment was significantly more common in YP compared to both IAP and EP (p < 0.001). Causes of permanent frontline TKI discontinuation during the first 12 months of treatment according to age at diagnosis are reported in the Table 1: among YP, 45 (14.9%) discontinued frontline TKI treatment due to hematologic toxicity (5 cases, 1.6%), extra-hematologic toxicity (11 cases, 3.7%), primary resistance (24 cases, 8.0%), secondary resistance (2 cases, 0.6%) or evolution in blastic phase (BP) (3 cases, 1.0%). Cumulative incidence of permanent discontinuation at 12 months was 14.6% (95%CI 10.7 - 18.5) in YP compared to 16.9% (95%CI 14.3 - 19.2) in IAP (p=0.388) and 24.0% (95%CI 20.9 - 27.1) in EP (p < 0.001) (Figure 1): considering only permanent TKI discontinuation due to treatment resistance (primary resistance + secondary resistance + evolution in BP), no difference was observed according to age at diagnosis [9.6% (95%CI 6.3 - 12.9) in YP versus 10.2% (95%CI 8.2 - 12.2) in IAP versus 11.8% (95%CI 9.6 - 14.0) in EP, p=0.589]. Conclusions Our data highlight the following peculiar clinical features at baseline and during the first year of treatment in YP with CML compared with IAP and EP: a delayed diagnosis, outlined by higher WBC count and rate of spleen enlargement; an expected choice of 2G-TKI as frontline treatment in the real-life, even if about one third of them was still treated with IM; a lower incidence of early frontline TKI permanent discontinuation compared to EP but not IAP, mainly due to toxic causes and not related to resistance. Data on early molecular response and further evaluations at 24 and 36 months are warranted to complete present analysis. Cavazzini:Novartis: Honoraria; Incyte: Honoraria; Pfizer: Honoraria. Bucelli:Novartis/Incyte: Honoraria. Bonifacio:Novartis: Membership on an entity's Board of Directors or advisory committees; Incyte: Membership on an entity's Board of Directors or advisory committees; Clinigen: Membership on an entity's Board of Directors or advisory committees; Pfizer: Membership on an entity's Board of Directors or advisory committees; BMS: Membership on an entity's Board of Directors or advisory committees. Sportoletti:Abbvie, Janssen, Beigene, Astra Zeneca, Takeda, Novartis: Membership on an entity's Board of Directors or advisory committees, Research Funding, Speakers Bureau. Stagno:Incyte, Novartis, Pfizer: Honoraria, Membership on an entity's Board of Directors or advisory committees, Speakers Bureau. Galimberti:Abbvie, Janssen, Novartis, Roche, Jazz, Astra Zeneca, Pfizer, Incyte: Speakers Bureau. Bocchia:Incyte: Honoraria; Novartis: Honoraria; BMS: Honoraria. Abruzzese:BMS: Consultancy, Membership on an entity's Board of Directors or advisory committees; Incyte: Consultancy, Membership on an entity's Board of Directors or advisory committees; Novartis: Consultancy, Membership on an entity's Board of Directors or advisory committees; Pfizer: Consultancy; Takeda: Consultancy. Breccia:BMS: Honoraria; Pfizer: Honoraria; Incyte: Honoraria; AbbVie: Honoraria; AOP: Honoraria; Novartis: Honoraria. Iurlo:Novartis, Pfizer, Incyte, BMS, GSK, AOP Health: Honoraria. Latagliata:BMS: Honoraria; Celgene: Honoraria; Janssen: Honoraria; Novartis: Honoraria. [Display omitted]